The Influence of Entrepreneurial Education and Family Support on Students' Interest in Entrepreneurship - Harun Basalamah, Salma; Clymenia, Agripina; Nofisks, Dara Jingga Puti; Fauziyah , Azizah; Nandang, Nandang (CV. Tripe Konsultan, 2024)
One of the main problems in Indonesia that affects the economy is unemployment. The unemployment rate in Indonesia in August 2023 was recorded at 5.32%, down from 5.86% the previous year. Entrepreneurial knowledge is an important concept in the world of business and entrepreneurship, which includes the understanding and skills needed to start and manage a business. To overcome this problem, the government encourages students to enter the world of entrepreneurship as an effort to overcome the gap between the number of workforce and available job opportunities. Entrepreneurial knowledge and entrepreneurial motivation are important factors that can influence students' interest in entrepreneurship. This study aims to examine the Influence of Entrepreneurial Knowledge and Family Roles on Entrepreneurial Interest in Entrepreneurship Study Program Students at the Indonesian Education University, the object of study is Entrepreneurial Interest, which acts as a dependent variable. Meanwhile, Entrepreneurial Knowledge and Family Roles act as independent variables. The subjects of this study were students of the Entrepreneurship Study Program at the Indonesian Education University. The results of this study can be concluded that entrepreneurial knowledge and the role of the family are the most important factors in forming an entrepreneurial behavior. The positive influence between entrepreneurial knowledge and the role of the family on the interest in entrepreneurship together will provide benefits in increasing student motivation and readiness to become entrepreneurs.